NeuproGemp, a polyphenol-rich botanical formula, ameliorates Alzheimer’s-like pathology in APP/PS1 mice via inhibition of human glutaminyl cyclase - Tseng, Tien-Sheng; Liaw, Chia-Ching; Shiao, Young-Ji; Huang, Ya-I; Cheng, Yu-Hsiu; Chen, Wang-Chuan; Tsai, Keng-Chang (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and amyloid-β (Aβ) accumulation. Increasing evidence suggests that dietary bioactive compounds may modulate neurodegenerative processes. Here, we evaluated the neuroprotective potential of NeuproGemp, a traditional Chinese functional food formula composed of Gastrodia elata, Paeoniae Radix Rubra, and the immunomodulatory protein GMI from Ganoderma microsporum, in APP/PS1 transgenic mice. Oral supplementation (300 mg/kg/day, 6–8 weeks) significantly improved ethological behaviors, including a ∼150% enhancement in burrowing performance (150 ± 25 g vs. 60 ± 40 g in controls), and reduced escape latency in the Morris water maze (Day 4: p < 0.05; Day 6: p < 0.01). Histological analyses demonstrated attenuated plaque-associated gliosis, with microglial/astroglial clusters reduced from 95 ± 22 to 55 ± 11 per section (p < 0.01), alongside increased hippocampal neurogenesis (DCX + cells: 49 vs. 18 cells/mm, p < 0.001). ELISA revealed reductions of ∼30% in soluble Aβ1-42 and ∼50% in pyroglutamate-modified Aβ3-42 (pE-Aβ3-42). High-performance liquid chromatography identified pentagalloylglucose (PGG) as the principal polyphenolic constituent of Paeoniae Radix Rubra, which exhibited potent human glutaminyl cyclase (hQC) inhibition (IC50 = 0.09 μM; KD = 63.7 nM). Molecular modeling and dynamics simulations further supported stable binding interactions of PGG and tannic acid with hQC. Collectively, these findings indicate that NeuproGemp, enriched in neuroactive polyphenols, exerts multi-targeted modulation of amyloidogenic pathways and represents a promising botanical intervention for mitigating AD-related neuropathology.